Scaling up of parenting support to prevent violence against children in Tanzania: insights from policymakers and service providers - Sabine van Tuyll van Serooskereken Rakotomalala; Kija Nyalali; Joyce Wamoyi; Onduru Gervas Onduru; Gerry Mshana; F. Marijn Stok; Mara A. Yerkes; John B. F. De Wit (Implementation Science Communications)
Abstract Background Evidence shows that parenting behaviours, including the use of violent discipline, can be changed through programmatic interventions. This study seeks to examine how policymakers and service providers in Tanzania perceive the provision of parenting support as a strategy to prevent violence against children and what the enabling and hindering factors are for the scale-up of existing evidence-based parenting supports. It does this by applying Daly’s analytical framework for parenting support. Methods Qualitative research was undertaken, with interviews conducted with 20 key informants consisting of purposively sampled policymakers and service providers. The interview data were analysed using inductive and deductive coding and analysis. Results The most prominent enabling factors noted for the scale-up of parenting support interventions in Tanzania include the existing supportive political commitment, the interventions currently on offer at the programmatic level, and the perceived understanding of Tanzanian caregivers of the importance of parenting and, thereby, a willingness to change. Current factors hindering the scale-up include the lack of a common understanding of what evidence-based parenting programmes entail, inadequate provision of human and financial capital to implement the programmes using community resources and deeply engrained social norms around adultism and gender. Conclusion Daly’s analytical framework allowed us to examine barriers and facilitators to scale-up the provision of parenting support to prevent violence against children, based on the viewpoints of policymakers and service providers. Understanding these barriers and facilitators will allow Tanzanian policymakers and service providers to further close the gap between the policies and the actual implementation of evidence-based parenting support programmes aimed at preventing violence against children.